2013
DOI: 10.1021/nn401037c
|View full text |Cite
|
Sign up to set email alerts
|

Robust Graphene Membranes in a Silicon Carbide Frame

Abstract: We present a fabrication process for freely suspended membranes consisting of bi- and trilayer graphene grown on silicon carbide. The procedure, involving photoelectrochemical etching, enables the simultaneous fabrication of hundreds of arbitrarily shaped membranes with an area up to 500 μm(2) and a yield of around 90%. Micro-Raman and atomic force microscopy measurements confirm that the graphene layer withstands the electrochemical etching and show that the membranes are virtually unstrained. The process del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…The rhombus shaped lattice (Fig. 2c) is comparable with the rhombus lattice of AB Bernal graphite prevailing in the literature20212223242526, where each white dot of the AB rhombus shaped lattice is due to amplification from the two overlapped atoms of the AB bilayer graphene (Fig. 3b).…”
Section: Resultssupporting
confidence: 65%
“…The rhombus shaped lattice (Fig. 2c) is comparable with the rhombus lattice of AB Bernal graphite prevailing in the literature20212223242526, where each white dot of the AB rhombus shaped lattice is due to amplification from the two overlapped atoms of the AB bilayer graphene (Fig. 3b).…”
Section: Resultssupporting
confidence: 65%
“…The strong asymmetry in the emission pattern also explains the observed enhancement of the Raman intensity of free-standing EG [33,34] which was prepared by locally removing the SiC substrate. Shivaraman et al [33] and Waldmann et al [34] observed that the G band intensity is enhanced by a factor of approximately two and five compared to measurements of SiC supported regions, respectively. In the case of the free-standing regions, the index of refraction is the same on both sides of the graphene, leading to a symmetric intensity distribution.…”
Section: Enhanced Collection Efficiency Of the Top-down Geometrymentioning
confidence: 75%
“…In the given material, eBLG, dense dislocation networks have been observed recently by dark-field transmission electron microscopy (TEM; ref. 10) after removing the SiC substrate 25 . Figure 2a shows a superposition of three distinct dark-field TEM images exhibiting a real partial dislocation network, taken from ref.…”
mentioning
confidence: 99%